Response of Physiological and Biochemical Parameters of Maize (Zea mays L.) to the Application of Zinc and Iron at Irrigation Cutoff Conditions - Mojtaba Afshari; Ahmad Naderi; Mani Mojadam; Shahram Lak; Mojtaba Alavifazel (Ikufīziyuluzhī-i Giyāhān-i Zirā̒ī)
This experiment was conducted to evaluate the effect of micronutrients on physiological, biochemical and functional characteristics of the of SC704 hybrid maize at water deficit condition during two cropping years of 2016-2017 and 2017-2018 at Experimental Farm in northwest of Ahvaz. The experiment was conducted as split-split plots based on a randomized complete block design with three replications. Main plots consisted of water deficit stresses at three levels, complete irrigation, cutoff irrigation both at the vegetative growth stage (12-14 leaf) and early seed growth stage, sub-plots were zinc sulfate foliar application at three concentrations (0, 5 and 10 g.L-1) and sub sub-plots foliar solution of iron sulfate at three concentrations (0, 3 and 6 g.L-1). The results of this study showed that increasing ZnSO4 concentration from zero to ten per thousand at constant levels of FeSO4 application (6 per thousand concentrations) resulted in increase in leaf area index under water deficit condition at the vegetative growth stage and beginning of seed growth stage. The lowest current photosynthesis was obtained in the absence of foliar application of zinc and iron. The lowest content of intercellular carbon dioxide was obtained at the beginning of seed growth stage when irrigation was stopped. The use of zinc and iron sulfate increased the values of this trait and removed the photosynthetic limitations. The highest yield of ear was obtained in complete irrigation with 6 per thousand concentration FeSO4 spray (9135.66 kg.ha-1), which increased by 25.1% compared to non-spray at this irrigation level.